Influence of couple stress size dependency in thermal instability of porous functionally graded composite microplates having different central cutouts - Zuo, Duquan; Sahmani, Saeid; Safaei, Babak; Ma, Guoling (Taylor & Francis Ltd, 2021)
In the present study, the isogeometric numerical solving process incorporating non-uniform rational B-splines is put to use to analyze the size-dependent thermal postbuckling behavior of porous functionally graded (FG) microplates having a central cutout with different shapes. Accordingly, the modified couple stress continuum elasticity is employed within the framework of a hybrid-type quasi-3D higher-order plate theory to take the through-thickness deformations into consideration by only four variables. On the basis of a refined power-law function together with the Touloukian scheme, the porosity-dependent as well as temperature-dependent material properties are achieved. The couple stress-based thermal postbuckling equilibrium paths are acquired corresponding to various geometrical and material parameters and different boundary conditions. It is found that the gap between thermal postbuckling equilibrium paths relevant to various patterns of the porosity dispersion is a bit higher for the couple stress-based case than the classical one. Furthermore, it is indicated that a central cutout causes to change the trend of the load-deflection response that leads to decrease the initial thermal postbuckling strength, while it enhances the microplate strength in deep thermal postbuckling region.
Keywords: Couple stress elasticity; porosity; isogeometric approach; functionally graded composites; quasi-3D plate theory